Improving methods for genotypic drug resistance testing in Mycobacterium tuberculosis - Mlamla, Zandile Cleopatra (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScMedSc)--University of Stellenbosch, 2011.